Efficient heterogeneous hydroboration of alkynes: enhancing the catalytic activity by Cu(0) incorporated CuFe2O4 nanoparticles - Zeng, Xianghua; Gong, Chunhua; Guo, Haiyang; Xu, Hao; Zhang, Junyong; Xie, Jingli (New journal of chemistry, 2018)
CuFe2O4 magnetic nanoparticles (NPs) are typically further calcined at high temperature to eliminate the reduced state of the Cu(0) source. Here we report the discovery of Cu(0) incorporated in CuFe2O4 that enables the catalytic activity for hydroboration of alkynes to be enhanced. This catalyst system has a low working temperature and short reacting time, and wide tolerance of substituted alkynes such as ynoate, ynamide and ynone. The Cu-CuFe2O4 catalyst was prepared by a simple hydrothermal method and well characterized by SEM, TEM, PXRD, XPS and EDS. Recycling of the catalyst was also achieved without obvious loss of activity after six runs. Furthermore, the mechanism of this reaction was also investigated.